Sustainability and Food Waste in Cooking Shows. On-Screen and Off-Screen Practices in MasterChef Italia - Innocenti, Veronica; Brembilla, Paola (Green Narratives, Ecology and Sustainability in Contemporary Television - Exploring Narrative Ecosystems, 2025)
This paper explores the integration of sustainability and food waste reduction themes in the program MasterChef Italia, the Italian installment of the global franchise, situating it within the broader context of lifestyle television’s growing responsibility to promote sustainable practices. First, we provide an overview of the history and formal features of food television and cooking shows, investigating how they can influence everyday practices and cultural norms; second, we explore the issue of food waste and sustainability related to the cooking shows genre; third, we focus on the case study and we analyze the program’s normative attitude towards what is “good” and “bad”; fourth, we detail its on-screen and off-screen sustainable practices and examine how these are portrayed to educate and influence both contestants and viewers. In so doing, we illustrate how MasterChef Italia positions itself as an exemplar within the framework of sustainable shows, embodying a normative approach to civic engagement. By turning sustainability into a best practice, the show highlights the potential of lifestyle television, particularly cooking shows, to promote environmental awareness and responsible living.